Vacancy induced enhanced photocatalytic activity of nitrogen doped CuO NPs synthesized by Co-precipitation method - Md Jannatul Ferdous Anik; Samiya Rahman Mim; Syed Sammo Swapno; Sirajum Munira; Oishy Roy; Md Muktadir Billah (Heliyon, 2024)
The chemical co-precipitation method, an effective approach in the synthesis of nanomaterials, was used to synthesize CuO nanoparticles (NPs). Structural and morphological modification of undoped and nitrogen (N) doped CuO nanoparticles were studied thoroughly using X-ray diffraction (XRD), FT-IR and field emission scanning electron microscope (FE SEM). Doping effect on defects was investigated using X-ray photoelectron spectroscopy (XPS), Raman spectroscopy and photoluminescence (PL) spectroscopy. Thus, the effect of doping on crystallinity, crystallite size, strain induced in lattice, defects and electron-hole recombination rate were investigated. Optical band gap was calculated using Kubelka-Munk function from the diffuse reflectance spectra (DRS) obtained using ultraviolet visible (UV–Vis) spectroscopy. Finally, photocatalytic performance was studied from rhodamine B (Rh B) degradation and reaction kinetics were analyzed. Maximum degradation efficiency was obtained for 1.0 mol% N doped CuO NPs which also exhibited minimum band gap and lowest electron-hole recombination rate. For the optimum doping concentration, nitrogen was found to create oxygen vacancies while substituting oxygen in the lattice, and thus reduce electron-hole recombination rate and increase photocatalytic degradation rate effectively.